2003
DOI: 10.1177/1077558703260272
|View full text |Cite
|
Sign up to set email alerts
|

Members’ Perceptions of Community Care Network Partnerships’ Effectiveness

Abstract: Investment in voluntary partnerships raises important questions: Should we invest in collaboration in moving toward the goals of health system redesign? What makes collaborative groups effective? Given the voluntary nature of these partnerships, membership perceptions of their experiences and the partnership's effectiveness should be important predictors of success. This article provides a preliminary analyses of perceived effectiveness of participants' perceptions of their own partnership, particularly focusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 21 publications
2
50
0
1
Order By: Relevance
“…Additionally, previous studies show that a relationship exists between both network size and network composition (in terms of heterogeneity of the network partners) and network performance (Brown et al 1998;Hasnain-Wynia et al 2003;Mitchell et al 2002;Zacocs and Edwards 2006). The direction of this relationship is not determined in the existing literature, although Hasnain-Wynia et al (2003) find that the larger the network, the lower the degree of its perceived effectiveness, and Brown et al (1998) determine that in order to achieve higher levels of network performance, it is necessary to cap the number of network members.…”
Section: Public Management Reviewmentioning
confidence: 85%
See 1 more Smart Citation
“…Additionally, previous studies show that a relationship exists between both network size and network composition (in terms of heterogeneity of the network partners) and network performance (Brown et al 1998;Hasnain-Wynia et al 2003;Mitchell et al 2002;Zacocs and Edwards 2006). The direction of this relationship is not determined in the existing literature, although Hasnain-Wynia et al (2003) find that the larger the network, the lower the degree of its perceived effectiveness, and Brown et al (1998) determine that in order to achieve higher levels of network performance, it is necessary to cap the number of network members.…”
Section: Public Management Reviewmentioning
confidence: 85%
“…The direction of this relationship is not determined in the existing literature, although Hasnain-Wynia et al (2003) find that the larger the network, the lower the degree of its perceived effectiveness, and Brown et al (1998) determine that in order to achieve higher levels of network performance, it is necessary to cap the number of network members.…”
Section: Public Management Reviewmentioning
confidence: 91%
“…First, resource munificence-defined as the level of resources available to the network from its environment reflecting the degree of uncertainty it faces in carrying out its activities-has a positive effect on network performance Provan & Milward, 2001;Shortell et al, 2002). At the same time, local communities with a history of collaboration, whose members recognize the value of collaboration and participate in public activities, are considered a healthier environment in which to ensure network functions (Hasnain-Wynia et al, 2003;Mitchell & Shortell, 2000;Zacocs & Edwards, 2006). System stability is another exogenous characteristic that can affect performance; more specifically, an unstable external environment has been identified as the key negative element against the overall effectiveness of networks (Hasnain-Wynia et al, 2003;Page, 2003;Provan & Milward, 1995).…”
Section: Hypothesis 1: Other Conditions Being Equal Bigger Network mentioning
confidence: 99%
“…Research on the size of the partnership has shown mixed results with no definitive explanation for whether size is a positive or negative characteristic of partnership group work (Williams & Allen, 2008). Some research has found that the larger the partnership, the lower the perceived effectiveness of the partnership (Hasnain-Wynia et al, 2003) and the less likely the partnership is to meet their stated goals ; yet no size range for effective collaboration has been cited. Further, some studies have found that more homogeneous compositions lead to less effectiveness (Hasnain-Wynia et al, 2003); whereas other studies have shown that heterogeneity is important to success (Zakocs & Edwards, 2006).…”
Section: Structural Characteristicsmentioning
confidence: 96%
“…Some research has found that the larger the partnership, the lower the perceived effectiveness of the partnership (Hasnain-Wynia et al, 2003) and the less likely the partnership is to meet their stated goals ; yet no size range for effective collaboration has been cited. Further, some studies have found that more homogeneous compositions lead to less effectiveness (Hasnain-Wynia et al, 2003); whereas other studies have shown that heterogeneity is important to success (Zakocs & Edwards, 2006). Though these concepts have been included as determinants of partnership success (Turrini et al, 2010), there appears to be no real consensus in the literature with which to include this determinant in analysis of collaboration effectiveness with any certainty.…”
Section: Structural Characteristicsmentioning
confidence: 97%